2017
DOI: 10.1002/ana.24950
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimethamine significantly lowers cerebrospinal fluid Cu/Zn superoxide dismutase in amyotrophic lateral sclerosis patients with SOD1 mutations

Abstract: ObjectiveCu/Zn superoxide dismutase (SOD1) reduction prolongs survival in SOD1‐transgenic animal models. Pyrimethamine produces dose‐dependent SOD1 reduction in cell culture systems. A previous phase 1 trial showed pyrimethamine lowers SOD1 levels in leukocytes in patients with SOD1 mutations. This study investigated whether pyrimethamine lowered SOD1 levels in the cerebrospinal fluid (CSF) in patients carrying SOD1 mutations linked to familial amyotrophic lateral sclerosis (fALS/SOD1).MethodsA multicenter (5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…More than 185 mutations in SOD1 have been reported to date [13]. Multiple efforts have focused on targeted therapeutic approaches for SOD1 -related ALS (ClinicalTrials.gov: NCT01041222: SOD1Rx [14]; NCT00706147: Arimoclomol [15]; NCT01083667: Pyrimethamine [16]).…”
Section: Introductionmentioning
confidence: 99%
“…More than 185 mutations in SOD1 have been reported to date [13]. Multiple efforts have focused on targeted therapeutic approaches for SOD1 -related ALS (ClinicalTrials.gov: NCT01041222: SOD1Rx [14]; NCT00706147: Arimoclomol [15]; NCT01083667: Pyrimethamine [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the level of sulfenic acid-modified wild-type SOD1 in CSF could be determined in living ALS patients. A few biomarkers for ALS, such as phosphorylated neurofilament heavy chain and TDP-43 in CSF, have been reported 52 54 , 57 59 . Our findings suggest that the quantification of sulfenic acid-modified SOD1 in CSF could have potential value as a diagnostic laboratory tool for sporadic ALS patients, and suggest a role of sulfenic acid-modified wild-type SOD1 as a diagnostic biomarker in sporadic ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, not all types of misfolded-SOD1 antibodies could detect pathological forms of wild-type SOD1 in CSF, but our study has suggested that wildtype SOD1 in CSF adopts a misfolded, toxic conformation(s) in pathological conditions of ALS and also a subset of PD and PSP. In that sense, it is important to note that levels of SOD1 in CSF of SOD1-ALS patients were reduced by oral medication with pyrimethamine [100].…”
Section: Misfolded Forms Of Sod1 In Cerebrospinal Fluid Of Alsmentioning
confidence: 99%